Food Acquisition Coping Strategies Vary Based on Food Security Among University Students - Emily Sklar; Gwen M Chodur; Leslie Kemp; Deborah S Fetter; Rachel E Scherr (Current Developments in Nutrition)
Background: Food insecurity on college campuses is a pressing issue, yet the ways in which students manage challenges and disruptions to their food security status (FSS) are poorly understood. Objectives: The objective of this study was to examine knowledge of food insecurity as a concept, evaluate FSS, identify food acquisition-related behaviors, and determine whether these behaviors differ among FSS. Methods: University students at increased risk of experiencing food insecurity (n = 43) were recruited for this mixed-methods study. Participants were surveyed about their FSS, coping strategies, and use of food access resources. Subsequent interviews occurred to evaluate their understanding of food insecurity as a concept and related food acquisition behaviors. The total number of coping strategies and food access resources used were quantified, and composite variables were created. Differences based on FSS classification were examined through regression analyses. Quantitative and qualitative data were integrated using concurrent triangulation. Results: Despite targeted recruitment efforts, 76% of participants were classified as food secure by the United States Department of Agriculture (USDA) Adult Food Security Survey Module (AFSSM). Participants were able to define food insecurity and identify circumstances that could contribute to an individual becoming food insecure. However, many participants described experiences that suggested the USDA AFSSM may not accurately capture students' true FSS. Most individuals faced significant challenges in maintaining food security. Participants used a series of coping strategies and food access resources to maintain or improve their food security, regardless of FSS, which included couponing, strategizing when food was low, and sharing food with housemates. Additionally, participants expressed concerns that their use of food access resources may deprive others with greater need. Conclusions: Results from this study shed insight on the complexities of food insecurity in the university setting, providing useful data to inform the development of better programs, outreach, and evaluation tools that encapsulate the many unique factors that make up FSS for students.